Essential and organizational transformations of economy management in the countryside as the basis of sustainable rural development in Ukraine - N.I. Strochenko; I.I. Koblianska (Marketing i Menedžment Innovacij, 2016)
The aim of the article. Despite the fact that agricultural producers significantly improve their economic activity in these latter days, rural areas in Ukraine are still on the downward path. This indicates the necessity to create responsible and effective economy management system in the countryside as organizational basis of sustainable rural development. Thus the article is aimed to determine the nature and directions of transformational changes of management practices in rural areas of Ukraine. Economy management way is considered as an integrating element of the bases and factors of sustainable rural development triad «nature – society – economy». The results of the analysis. There are analyzed the structure of the agricultural production sector in Ukraine and indicators of the wellbeing of households in rural and urban settlements. It is found that although personal farms appear as the main producers of certain agricultural products in Ukraine, they are excluded from the processes of the local area and community development. It gives accent to the need for essential and organizational transformations of the countryside economy management. It is proposed that personal farm should cover only own needs for food and related products, as a form of production organization without entrepreneur status. The provision of any services and products to external consumers (especially tourism and sales of agrifood products) should be considered in a plane of business and lead to the need to commission relevant legally significant actions such as: registration as a business entity or legal person as prescribed by law as well as the taxpayer under the tax Code of Ukraine. State policy should be based on the need for a system of stimulating business development instruments to ensure the implementation of these changes. These tools include, namely: promoting access to the public procurement market for local producers and manufacturers of organic products, implementation of public-private partnerships for developing social infrastructure, marketing promotion on the markets of innovative agricultural products and services. It is also important to establish mechanisms for monitoring compliance with the legal regime of entities with defined responsibility for violations in size that motivate the conduct of legal business. Given changes in law are suitable for additional local budget funds mobilization (in order of single tax, property tax, tourist tax payments). It should be noted that these financial resources are seemed to be negligible due to the current state of rural settlements and lack of control mechanisms for tax discipline of personal farm members. Conclusions and directions of further researches. The acquisition of the business status and commitments on tax and fees payments is seen primarily as an element of upbringing the following important sides: the new consciousness (business); the new responsibility (as a member of the community that uses shared resources, and therefore has to share the responsibility for the joint development); the new thinking (strategic and variable) and culture (business culture, a culture of joint action and communication, cultural interaction and participation in the processes of self-government, etc.). This is seen as an important step towards building a modern, diversified rural economy and sustainable rural development.